2017
DOI: 10.3390/rs9030201
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Calibration Set through Multivariate Analysis in Visible and Near-Infrared Prediction Model for Estimating Soil Organic Matter

Abstract: Abstract:The visible and near-infrared (VNIR) spectroscopy prediction model is an effective tool for the prediction of soil organic matter (SOM) content. The predictive accuracy of the VNIR model is highly dependent on the selection of the calibration set. However, conventional methods for selecting the calibration set for constructing the VNIR prediction model merely consider either the gradients of SOM or the soil VNIR spectra and neglect the influence of environmental variables. However, soil samples genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Liu et al further combined the Kennard-Stone algorithm and spectral pretreatment to choose representative calibration samples, and achieved an RPD of 1.85, which was still poorer than that obtained in the current study [59]. Wang et al proposed the MVARC-R-KS method to select representative calibration samples (not spectral variables as in the current study), which has resulted in good accuracy of PLSR models [61]. They reported that the best RPD was 1.81, which was also lower than the RPD in this study.…”
Section: The Effect Of Spectral Variable Selection Techniques On Model Accuracymentioning
confidence: 60%
“…Liu et al further combined the Kennard-Stone algorithm and spectral pretreatment to choose representative calibration samples, and achieved an RPD of 1.85, which was still poorer than that obtained in the current study [59]. Wang et al proposed the MVARC-R-KS method to select representative calibration samples (not spectral variables as in the current study), which has resulted in good accuracy of PLSR models [61]. They reported that the best RPD was 1.81, which was also lower than the RPD in this study.…”
Section: The Effect Of Spectral Variable Selection Techniques On Model Accuracymentioning
confidence: 60%
“…They [10] also considered geographical zones and spectral similarity, and observed homogeneous clusters. Other researchers performed clustering by using other variables, such as soil humidity, slope, parent material, and unsupervised Ward's Euclidian distance [25,28,31]. Clustering aims to correctly allocate the validation samples to the most similar group, and the SOC model based on that group can estimate the SOC of validation samples as accurately as possible.…”
Section: Effects Of Stratifying Samples By Soil Type In Soc Estimatiomentioning
confidence: 99%
“…Clustering aims to correctly allocate the validation samples to the most similar group, and the SOC model based on that group can estimate the SOC of validation samples as accurately as possible. In most cases, the model that estimates soil properties is improved by clustering the samples into homogeneous groups [10,25,41].…”
Section: Effects Of Stratifying Samples By Soil Type In Soc Estimatiomentioning
confidence: 99%
See 1 more Smart Citation
“…The performances were evaluated by R 2 p and RPD. The former value represents the quality of the data fitting when a given model is applied to another year, while the latter depicts the quality of the model transfer based on the prediction errors [34]. The results are shown in Figures 4 and 5. 0.7 for the other six years.…”
Section: Transferability Validationmentioning
confidence: 99%